All-biobased transparent-wood: A new approach and its environmental-friendly packaging application. (15th July 2021) - Van Hai, Le; Muthoka, Ruth M.; Panicker, Pooja S.; Agumba, Dickens O.; Pham, Hoa D.; Kim, Jaehwan
Graphical abstract: Highlights: All-biobased transparent-wood was prepared by impregnating cellulose nanofiber and chitosan into bleached wood. The transparent-wood showed good transparency, haziness, and UV shielding properties. The cellulose nanofiber and chitosan impregnated transparent-wood exhibited excellent mechanical and antioxidant properties. The all-biobased transparent-wood is applicable for environment-friendly packaging. Abstract: Transparent-wood (TW) is an emerging research topic that can be applied to biobased products. However, it is necessary to fill pores in TW with natural substances to prepare all-biobased TW. This paper reports an all-biobased TW by infiltrating cellulose nanofiber (CNF) and chitosan (CTS) suspensions into the bleached wood. CNF was isolated by combining the chemical and physical methods, and CTS was dissolved in acetic acid, and they were infiltrated into the pores of the bleached Fir veneer wood using a vacuum jar. The CNF and chitosan effects on the mechanical properties of the TW were studied, and the morphologies, crystallinity index, water contact angle, antioxidant, thermal degradation, and UV-shielding properties were investigated. The prepared TW showed 80 % total transmittance and 30–60 % haze, suitable for solar cell application. The all-biobased TW showed good thermal stability up to 315 °C and excellent UV shielding property for UV-B and UV-C. The antioxidant property of the CTS-TW significantly increased as compared to the original wood. The CNF-TW showed considerable tensile strength and yield strength of more than 200 % improved from the original wood. The potential for environment-friendly packaging applications was demonstrated by making a bag, medicine packaging, and straw for a drink.